Conceptualising (mathematics teacher educator) identity work: an enactivist-informed approach - Helliwell, Tracy; Ebbelind, Andreas (NOMAD Nordic Studies in Mathematics Education, 2024)
Research suggests that engaging in identity work is a vital part of a process of becoming a mathematics teacher and that mathematics teacher educators (MTEs) are key to supporting this process, yet we currently know very little about the identity work of MTEs themselves. In this paper, we contribute to this dearth of literature whilst exploring what the perspective of enactivism has to offer identity research given its emphasis on relationships and embodied action. We formulate our conceptualisation of MTE identity work as a set of seven methodological principles informed by the enactivist theory of cognition.